CULTURAL STUDIES: INSTITUTIONAL CRISIS OR THE TIME OF STRATEGIC DECISIONS - Irina Ya. Murzina (Образование и наука)
The aim of this investigation is to signify of the problems of cultural studies as a science and educational practice in a situation of modernization of education. The publication continues the discussion started at the alignment meeting of Heads of Cultural Studies Departments in Russia – «The science of culture and cultural education: time for strategic decisions». Methods. The author has applied the following methods: analysis of existing points of view; reflection of the essence of the cultural knowledge and perspectives of cultural development of cultural studies science in Russia. Results. The research outcomes show that cultural studies in modern Russia are experiencing institutional crisis: insufficient definiteness and awareness by experts and publicity due to places and roles of culturological disciplines in educational process, but also the methodological bases of activity of culturologists. Aspects of culturological formation are considered and prospects of its development are specified. It was proposed to continue the discussion started at the alignment meeting of Herzen State Pedagogical University of Russia, and it will give an option to discuss the solution ways of current recessionary situation more fundamentally and subjectively on territory-regional level. Scientific novelty. The approaches to understanding the culture as areas of scientific knowledge are methodized; the areas of cultural education in the conditions of modernization are summarized. Practical significance. The research implementations can be used while improving the theoretical-methodological component of cultural education, and extending the horizons for topical current research works in the field of cultural studies.